2010
DOI: 10.1111/j.1365-2435.2009.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between over‐winter survival and resting metabolic rate in juvenile North American red squirrels

Abstract: Summary 1.Resting metabolic rate (RMR) varies considerably among and within species. Two central questions in physiological ecology are whether values of RMR are repeatable and whether an association exists between RMR and fitness. 2. First, we investigated the repeatability of RMR in food hoarding, juvenile, North American red squirrels (Tamiasciurus hudsonicus Erxleben). Second, we explored links between RMR and survival. A low RMR may enhance survival if it reduces winter expenditure costs and ⁄ or allows m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 94 publications
5
111
2
Order By: Relevance
“…The significant repeatability of DEE in eastern chipmunks raises the possibility that this trait is heritable and thus may respond to selection (see Bergeron et al, 2011a), or be genetically correlated with other traits such as animal personality (Careau et al, 2008;Careau and Garland, 2012). An increasingly large number of studies report that RMR is significantly repeatable (reviewed by Duarte et al, 2010;Larivée et al, 2010;Nespolo and Franco, 2007) and heritable (reviewed by Careau et al, 2011). Despite the fact that we made several repeated measures on a large number of chipmunks, RMR was not repeatable in our population (sensu Bozinovic, 2007;Russell and Chappell, 2007).…”
Section: Repeatability Of Dee and Rmrmentioning
confidence: 87%
See 1 more Smart Citation
“…The significant repeatability of DEE in eastern chipmunks raises the possibility that this trait is heritable and thus may respond to selection (see Bergeron et al, 2011a), or be genetically correlated with other traits such as animal personality (Careau et al, 2008;Careau and Garland, 2012). An increasingly large number of studies report that RMR is significantly repeatable (reviewed by Duarte et al, 2010;Larivée et al, 2010;Nespolo and Franco, 2007) and heritable (reviewed by Careau et al, 2011). Despite the fact that we made several repeated measures on a large number of chipmunks, RMR was not repeatable in our population (sensu Bozinovic, 2007;Russell and Chappell, 2007).…”
Section: Repeatability Of Dee and Rmrmentioning
confidence: 87%
“…Because animals were not post-absorptive during respirometry measurements, we classified metabolic measurements as RMR rather than BMR. Thus, like many recent metabolic studies on small, wildcaught endotherms (Larivée et al, 2010;Speakman et al, 2004;Timonin et al, 2011), our RMR measurements include an unquantified metabolic contribution from the heat increment of feeding. Among small, granivorous rodents, RMR typically exceeds BMR by 5-15% with the difference becoming negligible after 3h of respirometry measurement (Nespolo et al, 2003).…”
Section: Limitationsmentioning
confidence: 99%
“…Third, juveniles that are born in summer and emerge in August-September should be very sensitive to beech availability because they only have one or two months to find their own burrow and accumulate a larder hoard for winter. In many species, the resources accumulated by juveniles, either as fat or food storage, greatly affect winter survival (e.g., Gaillard et al 2000, Larive´e et al 2010. During the summer 2009, chipmunks reproduced in anticipation of a mast, but beech seed production in autumn was very small, perhaps because chipmunks misread the cue to masting or that the masting event itself was impeded (e.g., by poor pollination).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the very few examples of studies on repeatability over long intervals on wild population of mammals, especially where reproduction must be involved, pointed in the opposite direction; suggesting no repeatability of RMR after reproduction. For example, the fact that Szafranzka et al (Szafranzka et al, 2007) only found repeatability after controlling for the seasonal effect and that Larivée et al (Larivée et al, 2010) did find repeatability over long intervals, but only for non-reproductive females in American red squirrels, may be due to a lack of flexibility of RMR after a reproductive event.The increase in RMRt we found here in post-lactating mice may be attributed in part to the incomplete reversal of the hypertrophy in the alimentary tract and associated organs such as the liver, heart and mammary glands, which is known to occur during lactation (Konarzewski and Diamond, 1995;Speakman and McQueenie, 1996; but see Johnson et al, 2001a). During the post-lactation period, adipose tissue replaces all glandular structures in the mammary gland in a process called involution, which occurs during the first 2 to 3days after weaning.…”
mentioning
confidence: 98%
“…In a wild population of North American red squirrels, repeatability of RMR, measured by Pearson's correlation coefficient was high (r0.77) over the short term (45-day interval) in reproductively active males and in non-reproductive females combined. However, over the long term (192-days interval) repeatability was significant (r0.72) only for non-reproductive females (Larivée et al, 2010). In a wild population of bank voles, repeatability of mass-independent BMR over long intervals (0.23; 54days) declined 32% in comparison with repeatability over short intervals (0.34; 5days); repeatability of absolute BMR showed a 47% decline over long intervals (Boratynski and Koteja, 2008).…”
mentioning
confidence: 99%